Dual -purpose exchange head charges - WU HAILIN (2016)
The utility model relates to a dual -purpose exchange head charges, including first converter and second converter, the both ends of first converter set up first socket and first plug respectively, the both ends of second converter set up second socket and second plug respectively, first converter with the centre of second converter is passed through the connecting rod and is connected. The beneficial effects of the utility model are that: carry dual -purpose exchange head charges, the charging wire that no matter possess android mobile phone still is the charging wire of apple cell -phone, all can charge to android mobile phone and apple cell -phone, possess apple and android mobile phone's people especially simultaneously, the time can only take a cell -phone charging wire in the trip, it is convenient to carry the comparison. 本实用新型涉及种充电两用交换头，包括第转换器和第二转换器，所述第转换器的两端分别设置第插口和第插头，所述第二转换器的两端分别设置第二插口和第二插头，所述第转换器和所述第二转换器的中间通过连接杆连接。本实用新型的有益效果为：携带本实用新型所述的充电两用交换头，无论拥有安卓手机的充电线还是苹果手机的充电线，都即能对安卓手机和苹果手机进行充电，尤其同时拥有苹果和安卓手机